Diastatotropis arofaniana sp. nov. from eastern Madagascar, a new species close to D. rubra Frieser, with a redescription of the type of the latter, and notes on morphology (Coleoptera: Anthribidae) - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2022)
Diastatotropis arofaniana Trýzna & Baňař sp. nov. (Anthribidae: Anthribinae: incertae sedis) is described as new from eastern Madagascar. Male and female genitalia are studied and illustrated, and colour photographs are provided. The new species is morphologically similar to D. rubra Frieser, 1992. A redescription of the female holotype of D. rubra, with the first illustrations of its habitus and genitalia are presented. Ecological notes, including colour photographs of the habitat of the new species, are provided. The curculionid type of hemisternites without toothed plates found in Diastatotropis is also discussed.